2007
DOI: 10.1200/jco.2007.25.18_suppl.7540
|View full text |Cite
|
Sign up to set email alerts
|

Oral talactoferrin extends survival in patients with refractory NSCLC in a randomized, placebo-controlled, phase 2 trial

Abstract: 7540 Background: Talactoferrin alfa (TLF), an immunomodulatory protein with a novel anti-cancer mechanism of action, was active preclinically and in non-small cell lung cancer (NSCLC) patients in Phase 1b studies. Randomized Phase 2 studies in NSCLC were conducted with TLF as a single agent and combined with chemotherapy. The 110-patient combination therapy study, which was previously presented (ASCO 2006, #7095), met its primary endpoint with an improved BOR over chemotherapy alone. We now present results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…However, in a follow-on trial designed to detect improvements in PFS or OS, it would be desirable to continue TLF/placebo until disease progression, particularly in view of significant OS improvements reported recently with single-agent TLF. 15 The median age of patients enrolled in this trial (approximately 55 years of age) is consistent with that reported in the literature for Indian patients with NSCLC 17 and is lower than the age of patients typically enrolled in clinical trials in Western populations.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, in a follow-on trial designed to detect improvements in PFS or OS, it would be desirable to continue TLF/placebo until disease progression, particularly in view of significant OS improvements reported recently with single-agent TLF. 15 The median age of patients enrolled in this trial (approximately 55 years of age) is consistent with that reported in the literature for Indian patients with NSCLC 17 and is lower than the age of patients typically enrolled in clinical trials in Western populations.…”
Section: Discussionsupporting
confidence: 85%
“…A similar reduction in AEs and grade 3/4 AEs was also observed in a second double-blind, placebo-controlled TLF trial-TLF monotherapy in patients with refractory NSCLC. 15 The majority of the AE reductions were in the four areas where reductions were expected based on lactoferrin's biological activities and previously available data. One major group of AE reductions was in thoraco-respiratory signs and symptoms, which are largely attributable to the NSCLC disease process itself.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…No drug-related serious AEs were reported. The incidence of AEs and grade 3 AEs were similar in both treatment arms [27].…”
Section: Safety and Tolerabilitymentioning
confidence: 74%
“…Two company sponsored trials (Agennix) have been conducted in patients with NSCLC. The first trial (LF-0201) was a randomized, double-blind, placebo-controlled, Phase II study of talactoferrin monotherapy in patients with locally advanced or metastatic NSCLC (Stage IIIB/IV NSCLC) who had failed first-or second-line chemotherapy [27]. A total of 100 patients were enrolled at 10 cancer centers in India and received one vial twice a day of either talactoferrin (1.5 g) or placebo given for up to three 14-week cycles of 12 consecutive weeks on followed by two weeks off study drug.…”
Section: Phase II Datamentioning
confidence: 99%